2017
DOI: 10.20524/aog.2017.0148
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adipokines in children with nonalcoholic fatty liver disease: possible noninvasive diagnostic markers

Abstract: BackgroundThe growing obesity pandemic is the leading cause for increasing prevalence of nonalcoholic fatty liver disease (NAFLD) in children. Histopathological evaluation of the liver remains the gold standard for NAFLD diagnosis, but it is an invasive procedure with a low but real risk of morbidity and mortality. The current study evaluated circulating chemerin and adiponectin as possible noninvasive diagnostic markers for NAFLD in obese non-diabetic children.MethodsA prospective case-control study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
(32 reference statements)
3
18
1
Order By: Relevance
“…Leptin, adipokines, such as adiponectin, and the newest one, chemerin, might have a role in the regulation of IR of obese children with NAFLD. 4,12,14 Leptin is one of the hormones which plays a significant role in sending the signals from the body fat to the brain. If the stored fat reaches the peak level, the leptin will send a signal to the brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leptin, adipokines, such as adiponectin, and the newest one, chemerin, might have a role in the regulation of IR of obese children with NAFLD. 4,12,14 Leptin is one of the hormones which plays a significant role in sending the signals from the body fat to the brain. If the stored fat reaches the peak level, the leptin will send a signal to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin was lower in obese children with NAFLD; meanwhile, chemerin is significantly higher in obese children with NAFLD as compared to the control group. 4 Based on the food recall data, subjects often consume foods with high GI during breakfast and dinner at their home. Since the family is not directly participating in the daily menu arrangement, it may result in an increase in IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were not able to show chemerin as a predictor of acute coronary syndrome [127]. Some studies showed a significant increase of chemerin level in non-alcoholic fatty liver disease (NAFLD) patients [128,129]. It was implied that this increase is connected with obesity [130].…”
Section: Adipokinesmentioning
confidence: 99%
“…Mohamed et al [26] Circulating adipokines in children with nonalcoholic fatty liver disease: possible noninvasive diagnostic markers…”
mentioning
confidence: 99%